2013
DOI: 10.7567/apex.6.075504
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Free-Standing GaN Substrates from Thick GaN Layers Crystallized by Hydride Vapor Phase Epitaxy on Ammonothermally Grown GaN Seeds

Abstract: Crystallization of GaN by hydride vapor phase epitaxy (HVPE) on ammonothermally grown GaN seed crystals is described. The initial growth conditions for HVPE are determined and applied for further bulk growth. Smooth GaN layers up to 1.1 mm thick and of excellent crystalline quality, without cracks, and with low dislocation density are obtained. Preparation of the free-standing HVPE-GaN crystal by slicing and structural and optical quality of the resulting wafer are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 9 publications
2
64
0
1
Order By: Relevance
“…3 Sochacki et al have shown that low dislocation density ammonothermally grown GaN crystals can be successfully used as seeds for the HVPE growth and it is possible to combine the benefits of both growth methods, ammonothermal growth method and HVPE, and crystallize low dislocation density GaN crystals. 4,5 The lattice parameter of the ammonothermal GaNseed material and the grown HVPE-GaN crystals had the same values within the experimental error (a = 318.97 ± 0.02 pm and c = 518.51 ± 0.01 pm) showing that no stress was introduced. Moreover the HRXRD 0002 rocking-curve full widths at half maximum (FWHM) of the HVPE crystals of approximately 40 arcsec were in the same order of magnitude as the ammonothermal seed material.…”
supporting
confidence: 57%
“…3 Sochacki et al have shown that low dislocation density ammonothermally grown GaN crystals can be successfully used as seeds for the HVPE growth and it is possible to combine the benefits of both growth methods, ammonothermal growth method and HVPE, and crystallize low dislocation density GaN crystals. 4,5 The lattice parameter of the ammonothermal GaNseed material and the grown HVPE-GaN crystals had the same values within the experimental error (a = 318.97 ± 0.02 pm and c = 518.51 ± 0.01 pm) showing that no stress was introduced. Moreover the HRXRD 0002 rocking-curve full widths at half maximum (FWHM) of the HVPE crystals of approximately 40 arcsec were in the same order of magnitude as the ammonothermal seed material.…”
supporting
confidence: 57%
“…A basic understanding of the sub-bandgap absorption behavior of GaN for wavelengths between 360 nm and 800 nm can be gleaned from the few existing reports which performed optical absorption measurements on epitaxial GaN films grown on sapphire substrates using photothermal deflection spectroscopy (PDS) 1,2,3,4 and optical transmission method 5 , along with a few isolated measurements using optical transmission measurements on bulk GaN crystals grown by the ammonothermal method 6 or hydride vapor phase epitaxy (HVPE) 7 . No report was found which systematically investigated the dependence of sub-bandgap absorption of high quality, bulk GaN crystals on free electron concentration (FEC).…”
Section: Introductionmentioning
confidence: 99%
“…Due to self-separation from the sapphire, a 2-inch free standing HVPE-GaN crystal can be obtained 15 . On the other hand, FS HVPE-GaN can be also obtained by using ammonothermally grown GaN as seed (Am-GaN) 16 . 1-inch Am-GaN crystals, with misorientation ~0.3 degree to the m direction and the (0001) surfaces prepared by mechano-chemical polishing and then cleaning to the epi-ready state, are used.…”
Section: Methodsmentioning
confidence: 99%